Réponses

Meilleure réponse !
2014-05-27T22:15:53+02:00
1)
 A=(-3x+6)(7x-4)-(-3x+6)(x-5)
A = -21x²+12x+42x-24-(-3x²+15x+6x-30)
A = -21x²+54x-24+3x²-21x+30
A = -18x²+33x+6

2)
A = (-3x+6)[(7x-4)-(x-5)]
A = (-3x+6)(7x-4-x+5)
A = (-3x+6)(6x+1)

3)
A = (-3x-2+6)(6x-2+1)
A = (6+6)(-12+1)
A = 12x(-11)
A = -132

2014-05-27T22:17:04+02:00
1)-21x au carré +12x+42x-24-(-3x au carré +15x+6x+30
=-21x au carré +54x-21+3x aucarré-x+30
=-18x au carré+s3x+6

2) A=(-3+6)(7x au carré-31x+20)
3)pour x=-2 A=452.352